The Effect of Direct Instructions Strategy Integrated Computational Thinking and Prior Knowledge on Critical Thinking and Problem-solving - Maulidah, Siti; Setyosari, Punaji; Kuswandi, Dedi; Ulfa, Saida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
In the current digital era, critical thinking and problem-solving skills are becoming increasingly important in everyday life, especially in the industrial era 4.0. One way to develop this ability is to use computational Thinking methods (CT). This research aims to test the effect of direct instruction strategy, integrated computational thinking, and prior knowledge on elementary schools' critical thinking and problem-solving skills in Heat and Changes in Science. The method used in this research is a quasi-experimental pretest-posttest non-equivalent control group design. This research was conducted at Madrasah Ibtidyah Ar-Rahmah Samarinda, involving 58 research subjects. The research instrument includes a prior knowledge test and critical thinking and problem-solving skills. To test the prerequisites for analysis using the normality test and homogeneity. Data analysis was used to test the research hypothesis using parametric statistics Tow Way MANOVA analysis technique. The research results show that (1) There are significant differences in critical thinking skills between groups of students who use computational learning and direct learning methods instructions; (2) critical thinking skills between groups of students with high prior knowledge are significantly from low prior knowledge; (3) There is no interaction between computational thinking and prior knowledge on students' critical thinking skills; (4) There are significant differences in problem-solving skills between groups of students who use computational learning and direct learning instructions; (5) The problem-solving skills of students with high prior knowledge is significantly different with low prior knowledge; (6) There is interaction between computational thinking and prior knowledge on students' problem-solving skills.